Pengaruh Penyetelan Mesin Menggunakan BB Gasohol E15 Terhadap Emisi - Sukardi, M.Pd Sukardi Sukardi; Agung M Pribadi; Abdi Sampurno (Jurnal Energi dan Teknologi Manufaktur, 2019)
Emissions produced by vehicles have a negative impact on human health and the environment, so steps need to be taken to reduce them. The use of a mixture of gasoline and alcohol (Gasohol) E15 fuels has a positive impact on reducing emissions. The number of conventional vehicles / cars that are still operating in Indonesia is generally prepared to use Gasoline only. If you want to use alcohol as a mixed fuel, you need a deeper study. The research objectives were to: 1) Test the effect of setting the ignition angle on CO and HC emissions, and 2) Test the effect of adjusting screw settings on CO and HC emissions. This research is using experimental method. The results showed that: 1) Standard adjustment has the lowest emission effect, and 2) there is an effect of Adjusting Screw settings on emissions.